2006
DOI: 10.1017/s0142716406060206
|View full text |Cite
|
Sign up to set email alerts
|

Continuity and shallow structures in language processing

Abstract: The core idea that we argued for in the target article was that grammatical processing in a second language (L2) is fundamentally different from grammatical processing in one's native (first) language (L1). Our major source of evidence for this claim comes from experimental psycholinguistic studies investigating morphological and syntactic processing in child and adult native speakers, and nonnative speakers who acquired their L2 after childhood and for whom their L1 is the dominant language. With respect to c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

19
188
3
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 184 publications
(212 citation statements)
references
References 52 publications
19
188
3
2
Order By: Relevance
“…In other words, L2 parses are flat and "shallow" compared to the more complex parses of native speakers. For morphosyntactic agreement, although L2 learners are predicted to compute it only between adjacent or nearby constituents (Clahsen et al 2006b), they are not predicted to decompose morphologically complex words (e. g., Clahsen et al 2010;Neubauer and Clahsen 2009;Silva and Clahsen 2008). These predictions are all qualitative inasmuch as they predict a difference between native speakers and L2 learners in the type of processes underlying sentence comprehension rather than a difference in one of its quantifiable dimensions (e. g., latency and/or size of processing effects).…”
Section: Theoretical Accounts Of Lprocessingmentioning
confidence: 96%
“…In other words, L2 parses are flat and "shallow" compared to the more complex parses of native speakers. For morphosyntactic agreement, although L2 learners are predicted to compute it only between adjacent or nearby constituents (Clahsen et al 2006b), they are not predicted to decompose morphologically complex words (e. g., Clahsen et al 2010;Neubauer and Clahsen 2009;Silva and Clahsen 2008). These predictions are all qualitative inasmuch as they predict a difference between native speakers and L2 learners in the type of processes underlying sentence comprehension rather than a difference in one of its quantifiable dimensions (e. g., latency and/or size of processing effects).…”
Section: Theoretical Accounts Of Lprocessingmentioning
confidence: 96%
“…Indeed, the results of previous experimental studies have shown that online sentence processing in a L2 involves many of the same reflexes exhibited by NSs when processing L1 input: rapid structuring of the input (Juffs & Harrington, 1995;Williams, Möbius, & Kim, 2001), use of lexical subcategorization information (Frenck-Mestre & Pynte, 1997), knowledge of island constraints (Omaki & Schulz, 2011), and sensitivity to prosodic cues (Dekydtspotter, Donaldson, Edmonds, Liljestrand-Fultz, & Petrush, 2008). However, another body of research has argued that-despite universal parsing routines-incomplete or impaired (i.e., nonnative) access to the grammatical rules of a given language may hinder sentence processing in real time, effectively eliminating any benefit of the detailed structural computations that are involved in using movement traces to resolve long distance wh-dependencies (Clahsen & Felser, 2006a, 2006b). Some previous L2 sentence processing studies have failed to detect robust evidence for traces in the structuring of input Marinis, Roberts, Felser, & Clahsen, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Although there appears to be considerable overlap in the characteristics of L1 and L2 sentence comprehension, salient L1/L2 processing differences include disparities in global performance (i.e., generally slower and less accurate performance in the L2; among others, see Cook, 1997;Frenck-Mestre, 2002;Hahne & Friederici, 2001), as well as differential sensitivity to certain morphosyntactic cues (Guillelmon & Grosjean, 2001;Jiang, 2004Jiang, , 2007Liu & Nicol, 2010;MacWhinney, 2002) and syntactic information (Marinis, Roberts, Felser, & Clahsen, 2005). These and other differences have been explained in terms of deficient L2 competence, even for highly proficient L2 users (Clahsen & Felser, 2006a;Jiang, 2004Jiang, , 2007; but see Clahsen & Felser, 2006b), as well as in terms of differences between the L1 and L2 processing systems. The latter class of accounts appeals to (among other factors) differences in automaticity (Hahne & Friederici, 2001;Jiang, 2004Jiang, , 2007Segalowitz, 2003), differences in the working memory resources available for processing in the L1 versus L2 (Kilborn, 1992), and interference (or transfer) from the L1 (or competition between language systems; Frenck-Mestre & Juffs, 1998a;Kilborn, 1989;MacWhinney, 2002; but see Barto-Sisamout, Nicol, Witzel, & Witzel, 2009).…”
mentioning
confidence: 99%
“…Yet another type of model holds that a semantic representation of a sentence can be computed (at least initially) without the construction of detailed phrase structure, based on heuristics such as "assume the first noun is the subject of the following verb," coupled with semantic information, lexical information, and real-world knowledge (Bever, 1970;Ferreira, 2003;Ferreira & Patson, 2007;MacWhinney, 1987;Townsend & Bever, 2001). 1 With regard to L2 sentence processing, a recent proposal by Clahsen and Felser (C&F;2006a, 2006b, 2006c holds that the third of these possibilities is the norm. Specifically, their shallow structure hypothesis (SSH) posits that "the syntactic representations adult L2 learners compute for comprehension are shallower and less detailed than those of native speakers," but that "L2 learners are able to draw on their lexical, pragmatic, and world knowledge to build up a semantic or conceptual representation of the sentence" (Clasen & Felser, 2006b, p. 32).…”
mentioning
confidence: 99%